Mesenchymal Stem Cell Derived Extracellular Vesicles Ameliorate Kidney Injury in Aristolochic Acid Nephropathy - Kholia, Sharad; Herrera Sanchez, Maria Beatriz; Cedrino, Massimo; Papadimitriou, Elli; Tapparo, Marta; Deregibus, Maria Chiara; Bruno, Stefania; Antico, Federica; Brizzi, Maria Felice; Quesenberry, Peter J.; Camussi, Giovanni (Frontiers in Cell and Developmental Biology, 2020)
Limitations in the current therapeutic strategies for the prevention of progression of chronic kidney disease (CKD) to end stage renal disease has been a drawback to improving patient recovery. It is therefore imperative that a solution is found to alleviate this problem and improve the health and well-being of patients overall. Aristolochic acid (AA) induced nephropathy, a type of nephrotoxic CKD is characterised by cortical tubular injury, inflammation, leading to interstitial fibrosis. Extracellular vesicles derived from human bone marrow mesenchymal stem cells (MSC-EVs) display therapeutic properties in various disease models including kidney injury. In the current study, we intended to investigate the ability of MSC-EVs on ameliorating tubular injury and interstitial fibrosis in a mouse model of aristolochic acid nephropathy (AAN). The chronic model of AAN is comprised of an intraperitoneal injection of AA in NSG mice, followed by a three-day incubation period and then inoculation of MSC-EVs intravenously. This routine was performed on a weekly basis for four consecutive weeks, accompanied by the monitoring of body weight of all mice. Blood and tissue samples were collected post sacrifice. All animals administered with AA developed kidney injury and renal fibrosis. A gradual loss of body weight was observed, together with a deterioration in kidney function. Although no significant recovery was observed in weight loss following treatment with MSC-EVs, a significant reduction in: blood creatinine and blood urea nitrogen (BUN), tubular necrosis, and interstitial fibrosis was observed. In addition, infiltration of CD45 positive immune cells, fibroblasts, and pericytes which were elevated in the interstitium post AA induced injury, were also significantly reduced by MSC-EVs. Kidneys were also subjected to molecular analyses to evaluate the regulation of pro-fibrotic genes. MSC-EVs significantly reduced AA induction of the pro-fibrotic genes α-Sma, Tgfb1 and Col1a1. A downregulation in pro-fibrotic genes was also observed in fibroblasts activated by AA injured mTECs in vitro. Furthermore, meta-analyses of miRNAs downregulated by MSC-EVs, such as miR21, revealed the regulation of multiple pathways involved in kidney injury including fibrosis, inflammation, and apoptosis. These results therefore suggest that MSC-EVs could play a regenerative and anti-fibrotic role in AAN through the transfer of biologically active cargo that regulates the disease both at a protein and genetic level.